Interaction Study of BCN OH ( Bicyclononyn ) and Pertuzumab in the Development of ADC ( Antibody Drug Conjugation ) Through Virtual Screening - Aden Dhana Rizkita1; Nisa Sri Wahyuni; Alwia, Nisa; Tris Ella Julita Gulo; Risma Eka Putri Selay; Ayu Andini Rizki Lestari Rohman; Efriyana Oksal; Kumam Pinky Chanu; Asaduzzaman; Taufik Muhammad Faqih5 (Prodi Kimia, 2024)
ADC (Antibody Drug Conjugation) is a complex molecule consisting of antibodies designed as a targeted therapy to treat disease, or a biologically active cytotoxic drug. Docking simulations of the pertuzumab antibody with the BCN OH ligand were carried out to see the interactions and stable conjugates between the antibody and the ligand as a form of ADC development using three software, consisting of Discovery Studio, pymol and pyrex. The pymol application is used for the preparation of pertuzumab, namely removing residues and water and is used to combine the ligand with the antibody, while the use of Pyrex Autodocx Vina is to determine the conformation of the ligand in binding with the macromolecule. Discovery studio is used to realize the bond between the linker and antibody and see the interactions that occur. This research aims to determine the interaction of pertuzumab with BCN OH as a starting point for selecting a suitable ligand for the ADC product so that later the ADC will be more stable until the target of the simulations carried out is obtained by the results of interactions that occur between pertuzumab and the BCN OH molecule. After being realized in two dimensions, it can be seen that there are amino acid compounds that bind to BCN OH on side B:103, there is lysine, side B:40 proline, side B:38 Arginine, side B:85 Threonine, and on side B:415 there is Air molecules. In the docking process, the presence of lysine bonds is an important factor in looking at the interaction of compounds with their macromolecules, considering that lysine is one of the residues that will bind to the functional groups on the linker to produce ADC products.